Amendment Thresholds and Voting Rules in Debt Contracts - CASKEY, JUDSON; HUANG, KANYUAN; SAAVEDRA, DANIEL (Journal of Accounting Research, 2026)
ABSTRACT Most loan contracts in the United States contain a provision for lender voting rules. We study the optimal voting rule that allows lenders to waive a covenant violation. When lenders have heterogeneous preferences, lenient voting rules increase the probability of waivers that allow inefficient investments. Stringent voting rules tend to allocate the marginal vote to lenders who deny waivers after false alarms so that they can renegotiate the loan to extract value from the firm, which incurs deadweight costs. In equilibrium, the optimal voting rule balances these two forces to improve contracting efficiency. We derive and empirically test comparative statics on how the optimal voting rule varies with lenders’ preferences and the borrower's accounting properties. Our model offers a rationale for the prevalent use of voting rule clauses in syndicated loan contracts.